Divergent transcriptional response to thermal stress among life stages could constrain coral adaptation to climate change - Ruggeri, Maria; Zhang, Yingqi; Aglyamova, Galina V.; Kenkel, Carly D. (Frontiers in Marine Science, 2023)
The ability for adaptation to track environmental change depends on how efficiently selection can act on heritable genetic variation. Complex life cycles may promote or constrain adaptation depending on the integration or independence of fitness-related traits over development. Reef-building corals exhibit life cycle complexity and are sensitive to increasing temperatures, highlighting the need to understand heritable potential of the thermal stress response and its developmental regulation. We used tag-based RNA-seq to profile holobiont gene expression of inshore and offshore Porites astreoides adults and recruit offspring in response to a 16-day heat stress, and larvae in response to a 4-day heat stress. Host developmental stage affected both broad patterns of host and symbiont expression, and modulated the stress response in both partners, suggesting that symbiotic interactions could vary between host developmental stages and influence the thermal stress response. Populations also exhibited origin-specific treatment responses, but response magnitude differed among life-stages. Inshore parents and recruit offspring exhibited a more robust stress response, exhibiting greater expression profile divergence and differentially expressing more genes compared to offshore-origin corals. This suggests genetic or epigenetic inheritance of regulatory mechanisms giving rise to expression plasticity, although ontogenetic plasticity as a result of the local reef environment during larval development could also explain the origin effect. However, larval populations exhibited the opposite response, with offshore larvae exhibiting a more robust stress response, possibly due to stage-specific effects or exposure duration. Overall, these results show that putatively adaptive regulatory variation persists in thermally naïve life stages, but thermally responsive genes are stage-specific, which could complicate the evolutionary response of corals to climate change.